UIN Sultan Maulana Malik Ibrahim's Strategy in Instilling Islamic Insight Students - Nurfitria, Nadia (Syntax Literate, 2021)
The Ministry of Religion is currently carrying out various strategies to prevent radical religious education and taking anticipatory steps to mainstream moderate religious understanding to anticipate radicalism movements.State Intelligence Agency (BIN) reported in 2017 about 37% of university students from a number of universities in Indonesia had been exposed to radicalism. Based on the data, it was also found that around 24% of university students and 23.3% of senior high school students were in agreement about the establishment of Islamic state in Indonesia. This finding has drawn the concern of PTKIN since it had become the basis for the spread of radicalism among the current millennial generation. PTKIN, as an educational institution and an institution under the Ministry of Religion's auspices, must help convey the value of Islamic insight to its students by teaching them. In the industrial era 4.0, UIN Sultan Maulana Malik Ibrahim Malang places a high priority on developing a planned and well-measured approach for infusing Islamic awareness in pupils. The existence of Ma'had al-Jami'ah UIN Maliki is one of the initiatives made, such as publishing an Islamic journal and training a cadre of ulama in public speaking for millennials. Workshops on Religious Moderation and conferences on the notion of Santri Dedication in Indonesian Deradicalization Efforts.